Identification of APOH polymorphisms as common genetic risk factors for venous thrombosis in the Chinese population. (23rd August 2014) - Tang, L.; Zeng, W.; Lu, X.; Wang, Q.‐Y.; Liu, H.; Cheng, Z.‐P.; Wu, Y.‐Y.; Hu, B.; Jian, X.‐R.; Guo, T.; Wang, H.‐F.; Hu, Y.
Summary Background Venous thrombosis (VT) is a worldwide medical problem. In order to identify individuals at high risk early, it is necessary to find more genetic risk factors. Nowadays, the studies on genetic factors of thrombosis are mainly focused on coagulation and anticoagulation factors. The exploration of other proteins involved in thrombosis and hemostasis may lead to a breakthrough. Objectives We used APOH as a candidate gene to investigate the existence of genetic variation that could increase the risk of thrombosis. Methods/Results In the current study, with a resequencing method followed by a case–control study, four polymorphisms (c.−32C>A, c.422T>C, c.461G>A, and c.1004G>C) in APOH (encoding β2‐glycoprotein I) were found to be in high linkage disequilibrium, which could result in three haplotypes. The H2 heterozygotes and H3 homozygotes had approximately 1.5‐fold and seven‐fold increased risks for VT, respectively. The minor allele frequency in the general population was 10%. In addition, H3 individuals showed a significantly decreased level of β2‐glycoprotein I, but an increased level of thrombin generation. Functional tests indicated that the mutant β2‐glycoprotein I had a significantly lower capacity to extend thrombin clotting time and increase thrombin generation potential. Conclusions This study revealed APOH as a new candidate gene associated with thrombosis, and further genetic research on this gene in patients in whom the cause of thrombophilia is unknown is therefore warranted.